Optimizing the immobilization conditions of β‐galactosidase on UV‐cured epoxy‐based polymeric film using response surface methodology. Issue 4 (10th March 2021) - Beyler‐Çigil, Aslı; Danis, Ozkan; Sarsar, Onur; Kahraman, Memet Vezir; Ogan, Ayse; Demir, Serap
Abstract: UV‐cured epoxy‐based polymeric film was prepared from glycidyl methacrylate, trimethylolpropane triacrylate, and poly(ethylene glycol) methylether acrylate. 2‐hydroxy‐2‐ methylpropiophenone was used as photo initiator. Covalent binding through epoxy groups was employed to immobilize β‐galactosidase from Escherichia coli onto this film, and immobilization conditions were optimized by the response surface methodology. ATR‐Fourier transform infrared (FTIR) and scanning electron microscopy (SEM) analysis was carried out to characterize the epoxy‐based polymeric film. Immobilization yield of β‐galactosidase on the material was calculated as 3.57 mg/g and the highest enzyme activity for the immobilized enzyme recorded at pH 6.5°C and 60°C. The immobilized enzyme preserved 51% of its activity at the end of 12 runs. Free and immobilized enzyme hydrolyzed 163.8 and 172.3 µM lactose from 1% lactose, respectively. Kinetic parameters of both free and immobilized β‐galactosidase were also investigated, and Km values were determined to be 0.647 and 0.7263 mM, respectively. Practical applications: In our study we prepared a UV‐cured epoxy‐based polymeric film and optimized the immobilization conditions of β‐galactosidase from Escherichia coli onto this polymeric film by using response surface methodology (RSM). For this purpose, three‐level and three‐factor Box–Behnken design, which is an independent, rotatable or nearly rotatable, quadratic design, was applied. Optimal levels of three variables, namely, the amount of enzyme, immobilization time, and pH were determined using Box–Behnken experimental design. Lactose hydrolysis studies were performed from milk and lactose samples using free and immobilized enzyme. In addition, kinetic parameters, storage stability, and re‐usability of immobilized β‐galactosidase were examined. Abstract : In our study we prepared an UV‐cured epoxy‐based polymeric film and optimized the immobilization conditions of β‐galactosidase from E. coli onto this polymeric film by using RSM. Lactose hydrolysis studies were performed from milk and lactose samples using free and immobilized enzyme. In addition, kinetic parameters, storage stability and re‐usability of immobilized β‐galactosidase were examined.